Penambahan Berat, Panjang, dan Lebar dari Ukuran Benih yang Berbeda pada Budidaya Kepiting Soka di Desa Mojo Kabupaten Pemalang - Muswantoro, Anggit Puji; Supriyantini, Endang; Djunaedi, Ali (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Soka crabs is also called soft-shelled crabs. Soft shell in crab was not because of different type of crab, but it is due to the crab just molted. Events of molting is marked with the release of the old shells and formed newly shells. This molting process produces an increase in body size (Growth). The experiment was conducted in September-October 2011. The research was conducted at Soka crab aquaculture in Mojo village, Ulujami Sub-District, Pemalang District. The method used in this study was field research, by using design random complete with 4 treatment 10 times deut.. Test animals used were the mud crab (Scylla serrata), a total of 40 crabs with initial weight size of 70-110 grams. Test animals were grouped into 4 groups of of weight, which were A (of weight 70-80 grams), B (80.1 to 90 grams), C (90.1 to 100 g) and D (100.1 to 110 grams). Each group of size consisted of 10 crabs. Test containers used were plastic box with a density of 1 individual / box. The results showed that the difference in weight grouping gave results that were not significantly different (p> 0.05) for weight, length and width after molting. Differences in weight grouping also gave different FCR values that were not significantly different (p> 0,05). This was probably due to the grouping of weight used was still relatively narrow. Mangrove crab survival rate level for all groups of size showed an average value of 100% and water quality was quite good and decent for soft-shelled crabs aquaculture.